FRI0599 A retrospective overview of clinical features, serology and histology of IGG4 related disease in hong kong: a dataset of 108 patients from four regional hospitals. (15th June 2017) - Tang, CP; Lee, KL; Lee, KW; Ng, WL; Wan, MC; Yuen, KY
Abstract : Background: IgG4 related disease (IgG4RD) is a spectrum of immune mediated disease with multiple organs involvement characterized by organ enlargement, function loss or obstructive symptoms (1, 2). Objectives: In this retrospective study, clinical, serological and histological features of IgG4RD patients over the past ten years from four regional hopsitals were reviewed. Methods: Four regional hospitals participated with study period from 1/1/2006 to 30/6/2016. IgG4RD patients were classifed into definite, probable and possible IgG4RD according to Japanese Comprehensive Diagnostic Criteria for IgG4RD (3). Statistical analysis: Association between the individual categorical covariates and the different organ involvement were analyzed by Fisher's exact test. Results: 108 patients were included. There were 81 male patients and 27 female patients and the male to female ratio is 3:1. The mean age of diagnosis was 62.8 year old. 57 patients were diagnosed as definite IgG4RD (53%), 14 patients as probable IgG4RD (13%) and 37 patients as possible IgG4RD (34%). Salivary glands involvement was the commonest, (M=45.7% vs F=33.3%), followed by pancreas (M=28.4% vs F=18.5%) and biliary system in male (M=24.7% vs F=11.1%) and orbital in female (M=23.5% vs F=18.5%). 53% patients also had multi organ involvement. 104 patients had serum IgG4 level checked and it was raised in 94 patients (90.4%). 77 patients (74.0%) had IgG4 level above twice upper limit of normal. IgG4 level was normal in 10 patients. 98% and 86.3% patients with multi organ involvement had IgG4 level >135mg/dL (p=0.016) and >270mg/dL (p=0.007) respectively. In the hepatobiliary group (n=36), 30 patients had blood checked for Ca19.9 level and it was raised in 17 patients (56.7%), with the highest level 14127 U/ml. 71 histological reports were available. Lymphoplasmacytic infiltration was a consistent features in all specimens (100%). Eosinophilic infiltration was seen in 19 specimen (27%). Fibrosis was seen in 44 specimens (63%). Sialadenitis and dacryoadenitis were associated with dense fibrosis. Obliterative phlebitis was seen in 7 specimens (10%). IgG4/IgG ratio was reported in 61 specimens. 53 specimens had IgG4/IgG ratio greater than 40% per high power field which accounted for 86.9% of the specimens. Conclusions: Most patients were male with the peak diagnosis at age 50 to 70. Salivary gland and pancreas were the most common organ involved. Most patients had a raised IgG4 level and most histological specimens showed a raised IgG4/IgG ratio on immunostaining. IgG4 level twice the upper limit of normal was quite specific for the disease and was associated with multi organ involvement. References: Pieringer H, et al. IgG4- related disease: an orphan disease with many faces. Orphanet journal of rare diseases. 2014;9:110. Haitao Du YW et al. IgG4-related disease and the curreny status of diagnostic approaches. EXCLI. 2012;11:651–8. Umehara H, et al. Comprehensive diagnostic criteria for IgG4-related disease (IgG4-RD), 2011. Modern Rheumatology. 2012;22(1):21–30. Disclosure of Interest: None declared